MORPHOLOGICAL DEVELOPMENT OF Napoleon WRASSE, Cheilinus undulatus LARVAE - Jhon Harianto Hutapea; Bejo Slamet (Indonesian Aquaculture Journal, 2006)
To improve the survival rate, napoleon wrasse larval rearing trial was conducted at Research Institute for Mariculture, Gondol-Bali in 2003. The trial aims at assessing initial feed for larvae, food habit, and morphological development from early larval stage to juvenile. The results showed that chicken egg yolk could be applied as initial feed and followed by rotifer, Artemia and mysid (Mesophodopsis sp.). Three swimming behavior of larvae were observed, drifting, free swimming and hiding on the substrate as larvae develop. Digestive system development, simple tube like, transition stage and coiled where digestive system could be distinguished between stomach, intestine and rectum.